Analysis and Detection of Heavy Metals Content in Some Selected Packaged Fruit Juices of Kathmandu City by Flame Atomic Absorption Spectroscopy - Paudel, Neeta; Dhakal, Agni; Pradhanang, Situ Shrestha (International Journal of Applied Sciences and Biotechnology, 2024)
The determination of level of heavy metals in packaged fruit juices is crucial, as extended exposure to even small quantities of these toxic element can cause severe health issues and chronic poisoning. Hence, it is essential to gather comprehensive data on the presence of heavy metals in packaged fruit juice samples. The objective of this research work is to determine heavy metals (Fe, Cu, Zn and Pb) in four different types of packaged fruit juice samples viz Apple, Mango, Orange and Lychee of four different popular brands bought from retail market of Kathmandu city by flame atomic absorption spectroscopy and compare with acceptable limit set by WHO/FAO. Wet acid digestion method was used for digestion process of packaged fruit juice samples. The concentration of Iron were ranged from 0.572-0.762mg/L in Orange juices; 0.362-0.624mg/L in Mango juices; 0.277-3.649mg/L in Apple juices; 0.279-1.770mg/L in Lychee juices respectively. Copper concentration were ranged from not detected (ND)-0.574mg/L in Orange juices; ND for all selected samples in Mango juices; ND- 0.023mg/L in Apple juices; ND-0.041mg/L in Lyclee juices. Similarly Zinc concentration were ranged from 0.0511-0.2026mg/L in Orange juices; ND-0.0700mg/L in Mango juices; ND for all selected samples in Apple juices; ND-0.0287mg/L in Lychee juices. The concentration of hazardous element Lead was found below detection limit in all selected packaged fruit juice samples. The heavy metals concentration in selected brand of packaged fruit juice samples was in following order: Fe>Zn>Cu> Pb. Int. J. Appl. Sci. Biotechnol. Vol 12(3): 158-165.